China's development: lessons for Africa - Matunhu, Jephias (Midlands State University, 2015)
There is ample statistical and non statistical evidence to confirm that China’s visibility within the global economic system has increased dramatically over the past three decades. Its share of world trade rose from less than 1 percent in 1979 to 5.2 percent in 2003. The dramatic growth of China over a relatively short space of time has attracted the attention of many Afro-optimistic development economists and policy makers. This desktop research investigates China’s development strategy with a view of drawing lessons for Africa’s development. Data were collected from literature on Africa and China’s socio-economic development trajectories. The study established that China had a unique socio-economic development strategy which was introduced in 1979. The carefully planned strategy has sustained the country’s remarkable development record. The question that begs attention is what lesson can Africa draw from the Chinese experience? Apparently, Africa is the least developing continent in the world, yet it is endowed with plenty economic resources.